2008
DOI: 10.1093/ndt/gfn343
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vancomycin use in chronic haemodialysis patients: room for improvement

Abstract: Although the initial indication for vancomycin use was generally appropriate, inappropriate continuation of this antibiotic, failure to obtain proper cultures to guide therapy and potentially subtherapeutic dosing regimens were some of the challenges identified. Centres providing chronic haemodialysis should take steps to optimize vancomycin prescription to improve clinical outcomes and reduce the risk of antimicrobial resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 15 publications
0
32
1
1
Order By: Relevance
“…Vancomycin was prescribed empirically for most cases in the study, which was deemed an appropriate indication due to the risk of MRSA infections in this patient group. Other studies where vancomycin is prescribed empirically before culture and sensitivities are available have also reported that 80–88% of vancomycin doses or courses are appropriate [18, 19]. Yet, once culture and sensitivities are available, vancomycin is commonly classified as inappropriate due to not fitting the criteria for infection or for failing to prescribe a narrower spectrum antibiotic [8, 18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Vancomycin was prescribed empirically for most cases in the study, which was deemed an appropriate indication due to the risk of MRSA infections in this patient group. Other studies where vancomycin is prescribed empirically before culture and sensitivities are available have also reported that 80–88% of vancomycin doses or courses are appropriate [18, 19]. Yet, once culture and sensitivities are available, vancomycin is commonly classified as inappropriate due to not fitting the criteria for infection or for failing to prescribe a narrower spectrum antibiotic [8, 18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Crawford and others, 23 who prospectively administered a single dose of vancomycin (35 mg/kg) at the end of dialysis, at a rate of 1 g/h, to 11 patients, reported that a once-weekly dose of vancomycin (35 mg/kg) did not achieve a vancomycin concentration of at least 10 mg/L before the third scheduled hemodialysis session. Zvonar and others 24 retrospectively evaluated 163 courses of vancomycin therapy in 105 patients at their institution and found that the most common dose was 500 mg after or during the hemodialysis session. Panais and others 25 administered a maximum loading dose of 1500 mg vancomycin in 38 courses, followed by 500 mg after each dialysis session and concluded that their protocol was successful in achieving a therapeutic trough concentration of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Erstens sollte deshalb die Gabe, wenn möglich, nach Dialyse erfolgen [16]. Zweitens sollte wie für Vancomycin gezeigt [17], auch bei anderen Antibiotika zusätzlich zur Erhaltungsdosis eine Supplementärdosis nach der Dialyse gegeben werden um die antimikrobielle Wirksamkeit zu gewährleisten.…”
Section: Dosisanpassung Bei Nierenersatztherapieunclassified